Hosay Trinidad : Muḥarram performances in an Indo--Caribbean diaspora - Korom, Frank J. (University of Pennsylvania Press, 2003)
"Hosay Trinidad contributes substantially to the anthropology of contemporary identity politics as well as to the study of 'boundaries' which has come to play a key role in important new lines of scholarship across the social sciences."--Anthropos